PSYCHOPEDAGOGICAL INTERVENTION IN CHILDREN WITH LEARNING DIFFICULTIES: CASE STUDY AT MALAPA ELEMENTARY SCHOOL (REMUNOM, 2026)
Psychopedagogical intervention in children with learning difficulties is an approach aimed at promoting strategies that enhance students’ cognitive, emotional, and behavioral development. The right to education for children with learning difficulties is recognized by normative instruments in Mozambique, reflecting the country's commitment to inclusive education. The Inclusive Education Plan and the Constitution of the Republic of Mozambique guide actions to ensure access, retention, and academic success through differentiated pedagogical practices. In this context, current realities show that many students with learning difficulties require psychopedagogical support. These frameworks encourage a multidisciplinary and personalized approach, emphasizing early and collaborative interventions involving professionals, teachers, and families.This study aims to understand the effectiveness of psychopedagogical intervention in improving the learning process of children with difficulties at Malapa Basic School. The research follows a qualitative approach, using semi-structured interviews conducted with six (06) participants for data collection. Data were analyzed through content analysis and triangulation techniques. The findings revealed that learning difficulties among the children studied result from interconnected family, emotional, and institutional factors. Regularly applied psychopedagogical strategies showed a positive impact, although some limitations were identified in planning and technical monitoring. The study concludes that it is essential to invest in professional training, provide adequate resources, and implement an integrated and well-coordinated psychopedagogical plan to improve learning outcomes.